Retrospective analysis of dermoscopic features of tinea capitis in 11 cases - Jiaguang SU; Sijian WEN; Wenyu LI; Jiacan HUANG; Wenjun ZHENG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective: To explore the dermoscopic characteristics of comma, spiral, malnourished hair, and to find out a new method for differentiation of Microsporum canis and Trichophyton tonsurans infections under the dermoscope. Methods: Dermoscopic characteristics were analyzed in 11 patients with tinea capitis who were positive for fungal smear and underwent dermoscopy at department of dermatology of the First Affiliated Hospital of Guangxi Medical University from 2019 to 2021. Results: Comma hair and malnourished hair were 100% and 80%, respectively, with no spiral hair, in patients infected by Microsporum canis. All patients with Trichophyton tonsurans infections had comma and spiral hair, and 66% had malnourished hair. That a patient with tinea capitis had comma, spiral, malnourished hair at the same time highly indicated Trichophyton tonsurans infections (χ2=8.00, P=0.18). Conclusions: Comma, spiral, and malnourished hairs are specific markers for the differentiation of Microsporum canis and Trichophyton tonsurans. Dermoscopy is a valuable approach in the diagnosis of Microsporum canis and Trichophyton tonsurans prior to fungal culture in patients with tinea capitis.